Pengaruh Kebudayaan Islam terhadap Arsitektur di Benua Asia - Muhammad Aslam Fauzan; Nadzif Ali Azhar T.; Mohamad Sugih Saputro; Raka Pramana Saputra; Vandah Ni’matim Barokah; Jenuri Jenuri (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Islamic architecture in the archipelago cannot be understood as simply a transfer of physical forms from the Middle East to Southeast Asia. It is the result of a deep cultural dialogue between universal Islamic principles and local wisdom that has been formed since pre-Islamic times. When Islam spread in the archipelago, it did not exist as a force that negates Hindu, Buddhist, and vernacular traditions, but rather proceeded through visual and structural synthesis that gave birth to a distinctive and hybrid Islamic architectural identity. One of the most iconic manifestations of this process is the use of overlapping roofs in historic mosques such as the Great Mosque of Demak and the Great Mosque of Banten. Different from typical Persian or Mediterranean stone domes, this multi-storey wooden structure is inspired by the concept of Meru in Hindu-Javanese architecture. The choice is not only symbolic, but also a functional adaptation to the tropical climate, as it allows for efficient rainwater disposal as well as optimal natural ventilation. Spatially, the placement of mosques follows the concept of Catur Gatra Tunggal, which is the integration of mosques with squares, government centers, and markets. This pattern reflects the integration between the spiritual, political, and economic life of the community. In the interior, the use of Saka Guru shows the appointment of local construction techniques as the main element of worship buildings. Aspects of syncretism are also seen in ornamentation, where pre-Islamic figurative motifs are transformed into flora and calligraphy patterns that are in harmony with the principles of Islamic aniconism. Thus, the archipelago's Islamic architecture represents Islam as an inclusive and contextual force that is able to process local traditions into a sustainable new identity.